Environmental an Ventilation Assessment in Child Day Care Centers in Porto: The Envirh Project - Mendes, A. (2014)
Children attending day care centers (CDCC) have been reported to be more prone to infectious diseases when compared with those cared for at home, and are exposed to conditions that may increase the risk of allergies and asthma. Several studies revealed that consequences of poor ventilation conditions include high levels of carbon dioxide (CO2) and many other indoor pollutants commonly detected in schools. Nine child day care centers were selected randomly to participate in this study. Fifty-two classrooms were assessed for chemical, biological, physical, and allergen parameters in spring and winter seasons in these nine CDCC located in Porto, Portugal. Outdoor measurements were also conducted for comparison. Our results indicated that (i) particulate matter (PM10) median levels were above the national reference levels, both by classroom type and by season; (ii) TVOC kindergarten peak values may raise some concern; (iii) CO2 was present at high median and maximum levels during spring and winter assessment in both nurseries and kindergartens classrooms; (iv) total bacteria concentrations were 57- and 52-fold higher in the nursery and kindergarten than outdoors, respectively, for the spring season; (v) winter and spring median predicted mean vote (PMV) indices were between “neutral” (0) and “slightly cool” (≤ –1) in the thermal sensation scale for comfort situations (−2 to 2) for both types of classrooms; (vi) there were significant differences for both PMV and predicted percentage of dissatisfied (PPD) indices by season; and (vii) CO2, total bacteria, and gram-negative bacteria were associated with low airflow rates. These data will help to evaluate the effectiveness of current building operation practices in child day care centers regarding indoor air quality and respiratory health.